The Paradox of Halal Branding: Navigating Religious Sincerity and Market Commodification in Indonesia's Middle-Class Economy - Aziz, Muhammad; Sholikah, Sholikah; Mujrimin, Bayu; Ghazali, Mohd Fahmi (El-Qist: Journal of Islamic Economics and Business (JIEB), 2026)
Abstract: Prologue: Halal branding in Indonesia has evolved beyond a religious requirement into a complex arena where spiritual authenticity intersects with market commodification. While intended to embody ethical compliance, the proliferation of halal labels among the expanding Muslim middle class has transformed "halal" into a competitive economic signifier. Despite extensive studies on consumer behavior, limited research critically examines the multipolar contestation among state authority, religious scholars, and market actors over how to navigate the tension between substantive religiosity and symbolic capital. Objective: This study aims to conceptualize the paradox of halal branding as a "hybridization" of religious, identity, and economic dimensions. It seeks to examine how this contestation shapes branding practices in Indonesia and evaluate its impact on religious sincerity through the lens of Maqāṣid al-Sharī‘ah. Methods: The research employs a qualitative approach combining an interdisciplinary literature review with field observations. Empirical data were gathered through the researcher's direct involvement in assisting Micro and Small Enterprises (MSEs) in the "SEHATI" (Sertifikat Halal Gratis; Free Halal Certification) program across Central and East Java (Semarang, Tuban, and Bojonegoro). The study utilizes a political economy of Islamic consumption framework, analyzed through reflexive thematic analysis, to map the shifting authority from the Indonesian Ulema Council (MUI) to the state (BPJPH) and its implications for market dynamics. Results/Findings: The findings demonstrate that halal branding in Indonesia operates through a "dual movement": the moralization of markets and the marketization of morality. Results indicate that while state-led certification (BPJPH) has democratized market access for MSEs, it has also triggered a contestation over "epistemic authority" between the state and the ulama. The study identifies that successful branding—exemplified by the cosmetics and tourism sectors—relies on a synergy in which religious values, modern identity, and economic logic reinforce one another. However, a significant paradox remains: the dominance of market rationality often leads to a "shallowing of meaning," where the halal label risks becoming a mere commodity, potentially displacing the substance of spiritual values. Contribution: This study enriches the sociology of religion and Islamic political economy by applying Abdul Majid an-Najjar's framework of maqāṣid al-sharī‘ah—specifically ḥifẓ al-mujtama' (protecting society) and ḥifẓ al-kiyān al-insānī (protecting human existence)—to evaluate market ethics. It proposes a balanced branding model that integrates institutional transparency with a religious narrative, providing a strategic framework for policymakers and businesses to ensure that halal branding enhances substantive religiosity rather than merely facilitating the commercialization of Islamic identity.